Association between demographics and knowledge of gestational diabetes mellitus (gdm) with fasting plasma glucose (fpg) among patients in Hospital Pakar Universiti Sains Malaysia (HPUSM) - Zain, Nur Najwa Mohd (Universiti Sains Malaysia, 2024)
Maintaining well-controlled glycaemic levels in patients with Gestational Diabetes Mellitus (GDM) is crucial to prevent adverse outcomes for both mother and child. Adequate knowledge about GDM is hypothesized to contribute to fasting plasma glucose level. This study investigated the association between the degree of knowledge regarding GDM with fasting plasma glucose among GDM patients. A cross-sectional study was conducted from April to June 2024, involving 60 GDM patients admitted to the Obstetrics and Gynaecology Ward at Hospital Pakar USM. Participants completed the GDM Knowledge Questionnaires (GDMKQ) with assistance, and their fasting plasma glucose levels were obtained from their medical records. A total of 60 patients were included in final analysis. The analysis of the five knowledge domains showed that the diet/food values domain had the highest mean score (0.93 ± 0.15), while basic knowledge of GDM domain had the lowest (0.57 ± 0.21). The study found no significant association between the level of knowledge and fasting plasma glucose (r = 0.143, p > 0.05). This weak correlation further indicates that knowledge alone may not be a strong predictor of glycaemic control. These findings suggest that other factors may influence glycaemic control in GDM patients. The P-value of 0.957 indicates no significant difference in knowledge scores across age groups. Similarly, parity showed no significant association with knowledge scores (P-value = 0.564) or FPG values (P-value = 0.912). The study concluded no significant association exists between demographics and knowledge about GDM with fasting plasma glucose among GDM patients. Patients aged 30-34 years, with a parity of one, who are working women, have a degree-level education, no family history of diabetes, and follow a diet control regimen recorded the highest mean knowledge scores and the lowest mean fasting plasma glucose levels. Further research is recommended to explore additional factors that may affect glycaemic levels which were not considered in the current study.